Hubungan antara Pola Asuh Orang Tua terhadap Prestasi Belajar Siswa Kelas V SDN Kp. Bulak II Pamulang Tangerang Selatan - Ramadhani, Vira; Amarullah, Ahmad; Saputri, Rahmawati Eka; Magdalena, Ina; Firdaus, M. Iqbal (MASALIQ, 2023)
This study aims to: (1) find out the parenting style given by the parents of fifth grade students at SDN Kp. Bulak II Pamulang (2) determines the learning achievement of fifth grade students at SDN Kp. Bulak II Pamulang (3) found the relationship between parenting style and student achievement in class V SDN Kp. Bulak II Pamulang. This study uses a correlative approach and uses quantitative methods. The subjects of this study were fifth grade students at SDN Kp. Bulak II Pamulang with a total of 34 students and this study also included parents of fifth grade students at SDN Kp. Bulak II Pamulang. The instruments used were parenting and student achievement questionnaires, and documentation. The collected research data were analyzed using data analysis techniques using the normality test, correlation test and linearity test. The results of the study regarding the relationship between parenting style and student achievement in class V SDN Kp.Bulak II Pamulang are as follows: (1) Parenting style given by parents of class V SDN Kp.Bulak II Pamulang is dominant authoritarian parenting style with a percentage of 61, 20%, while permissive parenting with a percentage of 37.40, and democratic parenting with a percentage of 1.7% (2) there is a significant relationship between parenting style and student achievement in class V. The implication of this research is that this research provides information to educators so that provide input or advice to parents of students in order to provide good parenting for children, so that children have good achievements in school.